BIOACTIVE COMPOUNDS OF RASAMALA (ALTINGIA EXCELSA NORNHA) LEAVES AS C-MYC PROTO ONCOGENE EXPRESSION SUPPRESSOR OF HUMAN TONGUE CANCER CELL IN VITRO - Risyandi Anwar; Arlette Setiawan; Supriatno Supriatno; Unang Supratman (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Tongue cancer is a common neoplasm found in oral cavity. It is characterized by aggressive cell growth, poor prognosis and being the cause of mortality. Objectives: to discover bioactive compounds of Rasamala leaves which possess an activity to inhibit SP-C1 human tongue cancer cell proliferation by reducing the expression of c-Myc proto oncogene. Methods: This is an experimental laboratory study using SP-C1 human tongue cancer cell. Separation of bioactive compounds from Rasamala leaves ethyl acetate extract was using various chromatography techniques guided by antiproliferative assay. Results: Two compounds were produced consisting of kaempferol (1) and quercetin (2). Compound 1 and 2 were tested to assess antiproliferative activity of kaempferol and quercetin upon SP-C1tongue cancer cell. IC50 values obtained from antiproliferative assay of each compound were 0.72 and 0.70 ug/ml respectively. Data analysis using ANCOVA test attained a significant value of α=0.05 and proceeded for probit analysis. The activity of  compound 1 and 2 was tested on c-Myc proto oncogene and it was acquired that compound 1 and 2 can suppress c-myc proto oncogene expression. Conclusion: Rasamala compounds consist of kaempferol (1) and quercetin (2) which possess an activity as tongue cancer cell proliferation inhibitor by reducing c-myc proto oncogene expression.